Assessment on serum CRP and serum ferritin level in COVID-19 patients of Dehradun Uttarakhand, India - Arya, Samiksha; Maqsood, Tariq; Ushmani, Rana; Prakash, Ved; Biswas, Sunny; Dar, M. Abass (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Since being declared a global pandemic, COVID-19 has ravaged many countries worldwide and has over-whelmed many healthcare systems. The pandemic has also resulted in the loss of livelihoods due to prolonged shutdowns, which have had a rippling effect on the global economy. Even though substantial progress in clinical research has led to a better understanding of SARS-CoV-2 and the management of COVID-19, limiting the continuing spread of this virus and its variants has become an issue of increasing concern, as SARS-CoV-2 continues to wreak havoc across the world, with many countries enduring a second or third wave of out-breaks of this viral illness attributed mainly due to the emergence of mutant variants of the virus. Our study tried to evaluate the fact regarding CRP and feritin parameters concentration efficacy in the detection and evaluation of inflammatory disorders, tissue injury and infections. Methods: CRP concentration measurements are useful in the detection and evaluation of inflammatory disorders, tissue injury and infections. The VITROS CRP slide method is performed using the VITROS 5600 integrated system. The VITROS CRP slide is a multi-layered, analytical element coated on a polyester support. The immune-rate format for CRP is based on enzymatic heterogeneous, sandwich immunoassay format. In this format a derivative of phosphorylcholine (PC) is covalently bound to polystyrene polymer beads and in the presence of calcium serves as a capture agent, monoclonal anti-CRP antibody conjugated to horseradish peroxidase (HRP) serves as a signal generator. Results: A total of 175 patients were selected for the study for estimate levels of C-reactive protein and serum ferritin in COVID-19 patients. The data obtained was coded and entered into Microsoft Excel Worksheet. Data was analysed and results were tabulated. In our study, serum CRP and serum ferritin values were found to be elevated in patients infected with COVID-19. Conclusions: CRP levels were positively correlated with lung lesions. CRP levels could reflect disease severity and should be used as a key indicator for disease monitoring. Serum ferritin was found to be elevated among the COVID-19 patients who could not survive the treatment as compared to the recovered patients. Therefore, serum concentrations of ferritin could be used as a prognostic marker in the management of COVID-19 patients which is easily available and cost effective too.